Grid-tied photovoltaic system based on PSO MPPT technique with active power line conditioning - de Oliveira, Fernando M; Oliveira da Silva, Sérgio A; Durand, Fábio R; Sampaio, Leonardo P; Bacon, Vinícius D; Campanhol, Leonardo B.G (IET power electronics, 2016)
This study presents a single-phase grid-tied photovoltaic (PV) system based on a global maximum power point tracking (MPPT) technique, which is performed by means of the particle swarm optimisation (PSO) method. The PSO-based MPPT technique is employed to solve problems related to mismatching phenomena, such as partial shading, in which the PV arrays are commonly submitted. Considering the search of the global maximum power point under partial shading, the effectiveness of the PSO-based MPPT technique is highlighted when compared with the well-known perturb and observe MPPT technique, since both the mentioned MPPT techniques are used to determine the dc-bus voltage reference to ensure a proper grid-tied inverter operation. A current generator algorithm based on a synchronous reference frame is proposed, which operates in conjunction with a dc-bus controller and MPPT algorithms, computing the reference current of the grid-tied inverter. In addition, the current generator controls the energy processed by the PV system to avoid over power rating of the grid-tied inverter, since the active power injection into the grid, reactive power compensation and harmonic currents suppression are carried out simultaneously. The performance and feasibility of the grid-tied PV system are evaluated by means of simulation and experimental results.